1993
DOI: 10.1111/j.1365-2958.1993.tb01176.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the RNA polymerase α subunit C‐terminal region in co‐operative interaction and transcriptional activation with OxyR protein

Abstract: The role of the alpha subunit of Escherichia coli RNA polymerase in transcription activation by the OxyR protein was investigated using in-vitro-reconstituted RNA polymerase containing alpha subunits carrying C-terminal truncations or an amino acid substitution. Mutant RNA polymerases failed to respond to transcription activation of the E. coli OxyR-dependent promoters. DNase I footprinting analysis indicates that the OxyR protein exerts a co-operative effect on the binding of wild-type RNA polymerase, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 16 publications
4
54
0
1
Order By: Relevance
“…BenM bound to Site 2 could activate transcription via contacts with RNA polymerase, as occurs for Class I activators (9,23,(31)(32)(33)(34). Consistent with a Class I type of activation, the Ϫ35 region of benA does not match the consensus for promoters with high affinity for RNA polymerase.…”
Section: Benm Is Tetramericmentioning
confidence: 86%
“…BenM bound to Site 2 could activate transcription via contacts with RNA polymerase, as occurs for Class I activators (9,23,(31)(32)(33)(34). Consistent with a Class I type of activation, the Ϫ35 region of benA does not match the consensus for promoters with high affinity for RNA polymerase.…”
Section: Benm Is Tetramericmentioning
confidence: 86%
“…Two LysR-type proteins, TrpI and OxyR, are known to be class I activators (14,21,42), and the Cys Ϫ phenotype of two rpoA mutants (encoding the ␣ subunit) suggests that CysB is also a member of this group (11,27). In addition, Bennett and Shi (2) have found that cysB is required for efficient expression of adi, the gene for a biodegradative arginine decarboxylase of E. coli, and that this process is defective in a strain containing one of these mutations, rpoA341, which results in an Glu-toLys change at amino acid residue 271 (44).…”
Section: Discussionmentioning
confidence: 99%
“…The OxyR protein belongs to the LysR family of transcription factors. Under activating conditions it binds as a tetramer near the −35 region of at least 20 regulon members (42) ( Table 2), and it stimulates transcription through direct contact with RNA polymerase (43). Activation by H 2 O 2 occurs through the oxidation of the Cys-199 residue to a sulfenic acid form.…”
Section: The Oxyr and Perr Regulators Of Responses To H 2 O 2 Stressmentioning
confidence: 99%